Occupational Ergonomics in Dentistry: Prevention of Musculoskeletal Disorders among Dental Professionals (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The prevalence of musculoskeletal disorders (MSDs) among dental professionals has become a significant occupational health concern worldwide. Dentistry involves prolonged static postures, repetitive fine motor movements, and sustained visual focus, which collectively contribute to cumulative musculoskeletal strain. This study explores the implementation of occupational ergonomics in dental settings as a preventive strategy for MSDs. By evaluating dental professionals across multiple clinical environments, we examine the effectiveness of ergonomic interventions—including posture training, adjustable chairs, optimized instrument placement, and workflow restructuring—on reducing physical strain and improving practitioner comfort. Our findings demonstrate a strong correlation between ergonomically optimized workplaces and lower incidences of musculoskeletal complaints, improved procedural efficiency, and enhanced long-term professional well-being. The research highlights the importance of integrating ergonomic principles into daily practice and professional education to mitigate occupational hazards and sustain a productive and healthy workforce in dentistry. This analytical work examines occupational strain experienced by dental professionals and evaluates preventive strategies aimed at minimizing work-related physical disorders. Daily clinical activities require sustained static postures, repetitive fine motor movements, and prolonged visual focus, which collectively contribute to cumulative physical overload. The analysis emphasizes how appropriate workplace adaptation, correct body mechanics, and evidence-based preventive measures significantly reduce the incidence and severity of musculoskeletal complaints. Attention is given to the interaction between practitioner posture, equipment design, and task organization. The findings demonstrate that systematic ergonomic integration enhances professional longevity, improves comfort during procedures, and supports consistent delivery of high-quality oral healthcare while reducing long-term disability risks.